Áp dụng hằng đẳng thức:x3+y3+z3−3xyz=(x+y+x)(x2+y2+z2−xy−yz−zx)⇔1−3xyz=1(1−xy−yz−zx)⇔3xyz=xy+yz+zxTa có:1=(x+y+x)2=x2+y2+z2+2xy+2yz+2zx⇔1=1+2(xy+yz+zx)⇔xy+yz+zx=0⇒3xyx=0⇔x=0 hoặc y=0 hoặc z=0+)Nếu x=0⇒{y+z=1y2+z2=1 và y3+z3=1Do đó suy ra đc:y2+2yz+z2=1⇒2yz=0suy ra:y=0;z=1 hoặc z=0;y=0Vậy ta có (x;y;z)=(0;0;1) hoặc (x;y;z)=(0;1;0
Áp dụng hằng đẳng thức:
x3+y3+z3−3xyz=(x+y+x)(x2+y2+z2−xy−yz−zx)⇔1−3xyz=1(1−xy−yz−zx)⇔3xyz=xy+yz+zxTa có:
1=(x+y+x)2=x2+y2+z2+2xy+2yz+2zx⇔1=1+2(xy+yz+zx)⇔xy+yz+zx=0⇒3xyx=0⇔x=0 hoặc y=0 hoặc z=0+)Nếu x=0
⇒{y+z=1y2+z2=1 và
y3+z3=1Do đó suy ra đc:
y2+2yz+z2=1⇒2yz=0suy ra:y=0;z=1 hoặc z=0;y=0Vậy ta có (x;y;z)=(0;0;1) hoặc (x;y;z)=(0;1;0
)